Bubble sorting in pinched microchannels for ultrasound contrast agent enrichment. Issue 18 (21st September 2015) - Kok, Maarten P.; Segers, Tim; Versluis, Michel
<x xml:space="preserve">Abstract</x> We present a lab-on-a-chip methodology for the enrichment of ultrasound contrast agents using pinched flow fractionation. We extend the modelling to include relatively large particles, by combining numerical and experimental results. Due to the simple operating principle, sorting devices based on this method are ideally suited for paralellization.